Implementing DirectAccess with Windows Server 2016 - Hicks, Richard M. (Apress, 2016)
Learn how to design, plan, implement, and support a secure remote access solution using DirectAccess in Windows Server 2016. Remote Access has been included in the Windows operating system for many years. With each new operating system release, new features and capabilities have been included to allow network engineers and security administrators to provide remote access in a secure and cost-effective manner. DirectAccess in Windows Server 2016 provides seamless and transparent, always on remote network connectivity for managed Windows devices. DirectAccess is built on commonly deployed Windows platform technologies and is designed to streamline and simplify the remote access experience for end users. In addition, DirectAccess connectivity is bidirectional, allowing administrators to more effectively manage and secure their field-based assets. Implementing DirectAccess with Windows Server 2016 provides a high-level overview of how DirectAccess works. The vision and evolution of DirectAccess are outlined and business cases and market drivers are explained. DirectAccess is evaluated against traditional VPN and this book describes the Windows platform technologies that underpin this solution. In addition, this book: Learn how to design, plan, implement, and support a secure remote access solution using DirectAccess in Windows Server 2016. Remote Access has been included in the Windows operating system for many years. With each new operating system release, new features and capabilities have been included to allow network engineers and security administrators to provide remote access in a secure and cost-effective manner. DirectAccess in Windows Server 2016 provides seamless and transparent, always on remote network connectivity for managed Windows devices. DirectAccess is built on commonly deployed Windows platform technologies and is designed to streamline and simplify the remote access experience for end users. In addition, DirectAccess connectivity is bidirectional, allowing administrators to more effectively manage and secure their field-based assets. Implementing DirectAccess with Windows Server 2016 provides a high-level overview of how DirectAccess works. The vision and evolution of DirectAccess are outlined and business cases and market drivers are explained. DirectAccess is evaluated against traditional VPN and this book describes the Windows platform technologies that underpin this solution. In addition, this book: Explains how the technology works and the specific IT pain points that it addresses Includes detailed, prescriptive guidance for those tasked with implementing DirectAccess using Windows Server 2016 Addresses real-world deployment scenarios for small and large organizations Contains valuable tips, tricks, and implementation best practices for security and performance.